THE PELATIHAN DENGAN PENDEKATAN METODE BOBATH LEBIH EFEKTIF DARI PADA PELATIHAN AKTIVITAS FUNGSIONAL UNTUK MENINGKATKAN KESEIMBANGAN BERDIRI STATIK PADA PASIEN STROKE SUB AKUT - PUTU ARTHA, I GUSTI (Majalah Ilmiah Fisioterapi Indonesia; Vol 1 No 3 (2013): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2013.v01.i03.p06)
Objective: to determine Bobath method exercise more efective than functional activity  exercise due to the increase of statical standing balance in sub acute stroke patien in 35-70 years group at physiotherapy policlinic of Rumah Sakit Indra Provinsi Bali. Method: eksperimental with 2 sample group, each 10 people. The first group was gived Bobath method exercise. The second group was gived fucntional exercise 12 times in a month. Result: there was a significant differen of statical standing balance in group I (with Bobath method) and group II (fucntional activity exercise) p=0,03 (p<0,05). Conclution: Bobath method exercise 12 times in a month more efective to increasing statical standing balance than fucntional activity exercise in sub acute stroke patient at physiotherapy policlinic of Rumah Sakit Indra Provinsi Bali.
Keywords: Bobath method, functional activity exercise, statical standing balance.